Initiative procurement documents : the difference between The United Kingdom and Malaysia / Nooriha Abdullah, Darinka Asenova and Stephen J. Bailey. - Abdullah, Nooriha; Asenova, Darinka; Bailey, Stephen J. (Universiti Teknologi Mara Selangor, 2016)
The aim of this paper is to analyse the risk transfer issue in Public Private Partnership/Private Finance Initiative (PPP/PFI) procurement documents in the United Kingdom (UK) and Malaysia. It utilises qualitative research methods using documentation and interviews for data collection. The UK documents (guidelines and contracts) identify the risks related to this form of public procurement of services and make explicit the appropriate allocation of those risks between the public and the private sector PPP/PFI partners and so the types of risks each party should bear. However, in Malaysia, such allocation of risks was not mentioned in PPP/PFI guidelines. Hence, a question arises regarding whether risk transfer exists in Malaysian PPP/PFI projects, whether in contracts or by other means. This research question is the rationale for the comparative analysis of documents and practices relating to risk transfer in the PPP/PFI procurements in both countries. The results clarify risk-related issues that arise in implementing PPP/PFI procurement in Malaysia, in particular how risk is conceptualised, recognised and allocated (whether explicitly or implicitly), whether or not that allocation is intended to achieve optimum risk transfer, and so the implications for achievement of value for money or other such objectives in PPP/PFI.